Case Report: identification of a novel 9.159-kb deletion in a Chinese α-thalassemia family using single molecule real-time technology sequencing - Wu, Shulin; Feng, Zonghui; Jiang, Fuxiang; Zhao, Min; Jiang, Peng; Xiao, Gang; Zhang, Xian (Frontiers in Genetics, 2025)
BackgroundThalassemia is one of the most common monogenic disorders worldwide and classified as α-thalassemia and β-thalassemia. Conventional methods for diagnosis of thalassemia, constrained by their focus on commonly known genotypes, can easily lead to missing or misdiagnosis of rare thalassemia genotypes.Case reportWe report the case of a 32-year-old pregnant woman with abnormal hematological parameters. Conventional gap polymerase chain reaction (Gap-PCR) and PCR-reverse membrane hybridization (PCR-RDB) were performed to analysis the 23 common thalassemia variants, but did not identify any pathologic variants. Next, we used PacBio third-generation sequencing platform based on single molecule real-time technology (SMRT) for this woman and her newborn and identified a novel 9.159-kb large deletion (chr16:165599-174758, GRCh38) of α-globin gene loci, which disrupted HBA2 gene. And the breakpoints of the deletion were validated by gap-PCR and sanger sequencing.ConclusionOur study identified a novel large deletion, which expanded the α-thalassemia gene variant spectrum and confirmed the efficiency of SMRT technology in detecting rare thalassemia variants, provided genetic counseling and prenatal intervention in clinical rare patients.